2013
DOI: 10.6023/a12090707
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigations on the Ferroelectricity of Graphene Oxides

Abstract: Graphene shows promise as a functional material in wide fields owing to its unique structures and properties. Here, as its parent material, graphene oxides have been observed exhibiting weak ferroelectric properties at room temperature. It is found that the one-dimensional hydrogen-bond chains generated by hydroxyls arranged in an orderly repeating pattern may play the key role in the electric ordering and may be responsible for this novel property of graphene oxide nanoribbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…1) and functional groups such as tertiary hydroxyl, 1,3-ether, ketone, quinine and phenol. 26,27 Qian-Wang In addition, it has now been confirmed that epoxy and hydroxyl groups will reside on the GO basal surface, while carboxyl groups tend to attach to the edges of the GO plane. 28,29 2.1.1.…”
Section: Introductionmentioning
confidence: 94%
“…1) and functional groups such as tertiary hydroxyl, 1,3-ether, ketone, quinine and phenol. 26,27 Qian-Wang In addition, it has now been confirmed that epoxy and hydroxyl groups will reside on the GO basal surface, while carboxyl groups tend to attach to the edges of the GO plane. 28,29 2.1.1.…”
Section: Introductionmentioning
confidence: 94%
“…21) and accompanied by the attachment of different types of functional groups, including tertiary hydroxyl, quinine, 1,3-ether, ketone and phenol. 249,251 The reported weak ferroelectricity of GO is attributed to the presence of surface-decorated functional and edge modied groups. 251 Different experimental and theoretical studies conducted on the magnetic behavior of rGO and GO reported anomalous behavior.…”
Section: Substitution Of Group Via Elements In Graphenementioning
confidence: 99%
“…249,251 The reported weak ferroelectricity of GO is attributed to the presence of surface-decorated functional and edge modied groups. 251 Different experimental and theoretical studies conducted on the magnetic behavior of rGO and GO reported anomalous behavior. Along with high room temperature ferromagnetism for GO and rGO, 252,253 diamagnetism, paramagnetism, superparamagnetism and antiferromagnetism were observed by different groups using different materials and different techniques.…”
Section: Substitution Of Group Via Elements In Graphenementioning
confidence: 99%
“…22which investigated the ferroelectricity of GO22, giving , with  = 502 and  = 1075 mm/kV. In our experimental condition, λ = 635 nm and d  = 1.5 nm.…”
Section: Resultsmentioning
confidence: 99%